A novel Leishmania infantum reference strain for gene editing and the study of visceral leishmaniasis - Rokhaya Thiam; Maria Santana Ceballos; Tom Beneke; Nada Kuk; Grégoire Pasquier; Lucien Crobu; Daniel C. Jeffares; Baptiste Vergnes; Bridlin Barckmann; Yvon Sterkers (PLoS ONE, 2025)
Parasites of the Leishmania donovani complex are responsible for visceral leishmaniasis, a vector-borne disease transmitted through the bite of female phlebotomine sand flies. As well as the human hosts, these parasites infect many mammals which can serve as reservoirs. Dogs are particularly important reservoirs. Transmission is widespread across Asia, Africa, the Americas, and the Mediterranean basin, including South of France. Visceral leishmaniasis poses a fatal threat if left untreated. Research into the pathophysiology of this neglected disease is of prime importance, as is the development of new drugs. In this study, we evaluated the growth, differentiation, and macrophage infectivity of four L. donovani complex strains and identified L. infantum S9F1 (MHOM/MA/67/ITMAP263, clone S9F1) as a well-adapted strain for genetic engineering studies. We present here the genome sequence and annotation of L infantum S9F1 T7 Cas9, providing the scientific community with easy access to its genomic information. The data has been integrated into the LeishGEdit online resource to support primer design for CRISPR-Cas9 experiments. We now aim to make this strain widely available to foster studies of visceral leishmaniasis.